Dynamics and pest and natural enemies dispersion in cowpea and colored cotton in sole or intercropping systems - Fernandes, Francisco Sales (2018)
Intercropping is an important cultural practice commonly used in pest management. It is based on the principle that the reduction of insect pest populations in the crop may occur due to the increase of agro-ecosystem diversity. The study was carried out aiming to assess the impact of colored fiber cotton-cowpea intercropping on both Aphis gossypii Glover, 1877 and Aphis craccivora Koch, 1854 (Hemiptera: Aphididae) aphid populations and their predators, especially Cycloneda sanguinea (Linnaeus, 1763) (Coleoptera: Coccinellidae). The study also aimed to evaluate the biomass production and the dispersion behavior of the aphids and their predators in this context. Experiments were carried out in laboratory, greenhouse and field conditions. Amino acids were extracted from cotton and cowpea plants. Under greenhouse conditions two wingless aphid species (A. gossypii and A. craccivora) and one predator species (C. sanguinea) were used to evaluate the dispersion, crop preference as well as predator progeny establishment. The influence of abiotic factors (temperature and relative humidity) in aphid dynamics was also analyzed. In field conditions the occurrence of arthropods found in sole or cotton and cowpea intercropped was evaluated. Mathematical models were developed to evaluate the aphid dynamics over time and statistical models were used to compare productivity in plants, dispersion, progeny and reproductive success of predator. Computational simulations were performed to compare the insect occurrence and to evaluate the best cropping system to pest reduction, natural enemy increase and plant productivity. Amino acid asparagine (ASP) was the most detected in the samples. Positive correlations were found between aphids and temperature. Negative correlations were found between aphids and relative humidity. Mathematical models described the dynamics behavior of aphids in arrangements studied. In all cropping systems an asymptotic growth was observed, with population peak and decrease in aphid population. Under greenhouse conditions, the sole cropping exhibited higher number of aphids than intercropping systems. The natural enemy dispersion was similar in both cropping system. However, the progeny abundance and cotton productivity were higher in treatment t1 (intercropping designed with cotton plants : cowpea plants in a row, started and ended with cotton plants). Simulations based in field experiments and literature showed that some cropping arrangements provided temporal dynamics stable in arthropods. However, Toxomerus watsoni (Curran, 1930) (Diptera: Syrphidae) exhibited temporal dynamics unstable and less abundance in arrangements of sole organic cotton or cotton-cowpea intercropping t1 that received insecticide for sucking pest control. Computational simulations confirmed that biomass production was higher in some cotton-cowpea intercropped than in sole cropping systems.